2006
DOI: 10.1111/j.1442-9071.2006.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Cataract and its surgery in Papua New Guinea

Abstract: Increasing the quantity and quality of cataract surgery need to be priorities for Papua New Guinea eye care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Evidence continues to grow in support of women having lower access to cataract surgery, particularly in developing regions 10 . Education of female members within the community may therefore bring about a more sizeable reduction in the burden of low vision and blindness in the region 10–12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence continues to grow in support of women having lower access to cataract surgery, particularly in developing regions 10 . Education of female members within the community may therefore bring about a more sizeable reduction in the burden of low vision and blindness in the region 10–12 …”
Section: Discussionmentioning
confidence: 99%
“…10 Education of female members within the community may therefore bring about a more sizeable reduction in the burden of low vision and blindness in the region. [10][11][12]…”
Section: Discussionmentioning
confidence: 99%
“…However, among a rural Chinese population, Li et al 22 found cataract VI prevalence of 4.6% and cataract blindness of 1.3%. Also in Papua New Guinea, 23 a cataract VI prevalence of 7.4% (95% CI 6.4-10.2) was reported.…”
Section: Eyementioning
confidence: 96%
“…The Rapid Assessment of Cataract Surgical Services survey on people 50 years and older in PNG estimated the prevalence of visual impairment was 29.2 per cent with blindness at 8.9 per cent . The major causes of visual impairment among those 50 years and older were refractive error (13.1 per cent) and cataract (6.4 per cent); however, the cataract surgical coverage was 45.3 per cent and the visual outcomes of cataract surgery were found to be poor . A recent survey on a convenience sample of participants attending outreach clinics identified 4.8 per cent had corneal/retinal diseases …”
mentioning
confidence: 99%